Hyper-accumulation of starch and oil in a Chlamydomonas mutant affected in a plant-specific DYRK kinase. Issue 1 (December 2016) - Schulz-Raffelt, Miriam; Chochois, Vincent; Auroy, Pascaline; Cuiné, Stéphan; Billon, Emmanuelle; Dauvillée, David; Li-Beisson, Yonghua; Peltier, Gilles
Abstract Background Because of their high biomass productivity and their ability to accumulate high levels of energy-rich reserve compounds such as oils or starch, microalgae represent a promising feedstock for the production of biofuel. Accumulation of reserve compounds takes place when microalgae face adverse situations such as nutrient shortage, conditions which also provoke a stop in cell division, and down-regulation of photosynthesis. Despite growing interest in microalgal biofuels, little is known about molecular mechanisms controlling carbon reserve formation. In order to discover new regulatory mechanisms, and identify genes of interest to boost the potential of microalgae for biofuel production, we developed a forward genetic approach in the model microalgaChlamydomonas reinhardtii . Results By screening an insertional mutant library on the ability of mutants to accumulate and re-mobilize reserve compounds, we isolated aChlamydomonas mutant (starch degradation 1, std1 ) deficient for a dual-specificity tyrosine-phosphorylation-regulated kinase (DYRK). Thestd1 mutant accumulates higher levels of starch and oil than wild-type and maintains a higher photosynthetic activity under nitrogen starvation. Phylogenetic analysis revealed that this kinase (named DYRKP) belongs to a plant-specific subgroup of the evolutionarily conserved DYRK kinase family. Furthermore, hyper-accumulation of storage compounds occurs instd1 mostly under low light in photoautotrophic condition, suggesting that the kinase normally acts under conditions of low energy status to limit reserve accumulation. Conclusions The DYRKP kinase is proposed to act as a negative regulator of the sink capacity of photosynthetic cells that integrates nutrient and energy signals. Inactivation of the kinase strongly boosts accumulation of reserve compounds under photoautotrophic nitrogen deprivation and allows maintaining high photosynthetic activity. The DYRKP kinase therefore represents an attractive target for improving the energy density of microalgae or crop plants.